Mobile Assisted Language Learning (MALL) to Enhance English Language Learning: Ideas and Constraints - Hidayat, Ade (Jurnal Pendidikan Vokasi Raflesia, 2024)
This article focuses on ideas and constraints in utilizing smartphones in language learning. Mobile Assisted Language Learning (MALL) needs to be explored more by the teachers and curriculum developers as the use of mobile devices is massively widespread. Considering students' access to smartphones, internet access, also the cost, practical usage, and workload in implementing MALL, it is important then to see what ideas that can be implemented in language learning activities by utilizing smartphones. The ideas in implementing MALL include utilizing features available in smartphones such as camera features, audio recording features, messaging and chatting application, social media engagement, language learning application, and learning management system. This article also proceeds to describe the possible constraints in implementing the ideas which have to be overcomed to make an effective language learning design involving smartphones as pedagogical tools. As mobile devices have already become parts of daily activities, therefore language learning teachers and curriculum develovers have to utilize them and design mobile-assisted learning activities that can help students to get more experience in learning a language.